Nerve growth factor-induced PKB/Akt activity is sustained by phosphoinositide 3-kinase dependent and independent signals in sympathetic neurons. - Virdee, K; Xue, L; Hemmings, B; Goemans, C; Heumann, R; Tolkovsky, A (1999)
Phosphoinositide 3-kinase and its downstream effector kinase PKB/Akt have been suggested to have crucial roles in suppressing apoptosis in several classes of neurons. However, few studies have conducted a long-term investigation of either kinase activity, many studies relying instead on use of the phosphoinositide 3-kinase inhibitors wortmannin and LY294002. When we added LY294002 or wortmannin to sympathetic neurons, apoptosis in the presence of nerve growth factor (NGF) was very slow compared to that obtained by NGF deprivation. However, expression of a kinase-inactive mutant of PKB/Akt in the presence of NGF induced apoptosis in a significant proportion of the neurons. To understand this discrepancy, we investigated more closely the regulation of PKB/Akt activity by NGF. NGF stimulation induced a rapid increase in PKB/Akt activity which was sustained at approximately 6-fold up to 24 h. Phosphoinositide 3-kinase was also rapidly activated by NGF. However, concentrations of wortmannin which completely blocked phosphoinositide 3-kinase activity in the neurons inhibited no more than 50-70% of cellular PKB/Akt activity. Similarly, approximately 50% of maximal NGF-stimulated PKB/Akt activity remained elevated at concentrations of LY294002 which completely blocked neurite outgrowth, a process known to be phosphoinositide 3-kinase dependent. We suggest that a proportion of the sustained PKB/Akt activity induced by NGF is mediated by phosphoinositide 3-kinase-independent pathways. These results raise a cautionary note as to the usefulness of LY294002 or wortmannin as tools to dissect the role of PKB/Akt in neuronal survival.